Electrostatically Assembled Sb2S3/MXene Nanocomposites As Anode Materials for High-Performance Lithium-Ion Batteries - Lei Bai; Cheng, Fangming; Dong, Yuting (Russian Journal of Physical Chemistry A, 2025)
— Antimony sulfide (Sb 2 S 3 ) possesses a high theoretical capacity and excellent reversibility, making it a promising anode material for lithium-ion batteries (LIBs). However, its poor intrinsic conductivity and significant volume changes during charge/discharge cycles severely limit its cycling stability and rate performance. In this study, a novel composite material was synthesized by electrostatically assembling Sb 2 S 3 nanowires (Sb 2 S 3 nw) onto MXene nanosheets as a potential anode material (SbSMX). The introduction of highly conductive MXene substrates enhances electron transfer between the distinct interfaces of Sb 2 S 3 and MXene. Additionally, the constructed 1D–2D structure promotes ion transport within the electrode, while the mechanical flexibility of MXene effectively mitigates the severe volume expansion of Sb 2 S 3 . As a result, the SbSMX composite exhibits a high capacity of 813 mA h g –1 at a current of 50 mA g –1 , stable cycling performance with a capacity of 735 mA h g –1 after 100 cycles at 100 mA g –1 (88% retention), and excellent rate capability, achieving 466 mA h g –1 at a current of 3 A g –1 .